Morphological and cytogenetic description of a new species of Parasitylenchus Micoletzky, 1922 (Tylenchida, Allantonematidae) parasitizing Harmonia axyridis (Pallas, 1773) (Coleopera, Coccinellidae) in Argentina - Camino, Nora B. (2019)
Parasitylenchus pseusobifurcatus sp.n. ( Tylenchida, Allantonematidae) is described for the first time for Argentina as a parasite of adults of Harmonia axyridis (Pallas, 1773) (Coleopera, Coccinellidae). The new species is closed to P. bifurcatus Poinar Jr. & Steenberg, 2012, by the characteristic of having the tail tip of all vermiform females and immature males bifurcated, but they differ by the size of the gubernaculum. Its karyotype formula is described. Publicación registrada en Zoobank:LSIDurn:lsid:zoobank.org:pub:751C7C95-EDD7-4D3F-80FA-0BBC5339E404 Acto nomenclatural:LSIDurn:lsid:zoobank.org:act:31912097-A9DF-47C5-9294-2E9DEA879AED